2016
DOI: 10.1038/srep29227
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response against host-mimetic homologous epitopes of Mycobacterium avium subsp. paratuberculosis in Japanese multiple sclerosis patients

Abstract: Several works have demonstrated the existence of a link between Mycobacterium avium subsp. paratuberculosis (MAP) and MS in Italy. In this study, we analyzed the serology of MAP in a Japanese population while looking at several markers of MAP. Fifty MS patients, 12 clinically isolated syndrome (CIS) patients, 30 other neurological disorders (OND) patients, and 50 healthy controls (HCs) were tested using ELISA for the presence of IgG antibodies toward immunodominant epitopes MAP_0106c121-132, homologues MBP85-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
4
30
1
Order By: Relevance
“…Detection of MAP in 2–4 million patients with ulcerative colitis (UC) has been documented/speculated upon [ 73 ]. However, only 13 research documents considered MAP in connection to UC throughout the study period [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Growth of MAP research linked with UC had a negative growth rate of –30% ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Detection of MAP in 2–4 million patients with ulcerative colitis (UC) has been documented/speculated upon [ 73 ]. However, only 13 research documents considered MAP in connection to UC throughout the study period [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Growth of MAP research linked with UC had a negative growth rate of –30% ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacterium avium subspecies paratuberculosis (MAP) is accepted as the cause of Johne's Disease (JD) [1], a chronic diarrheal wasting disease of cattle and a wasting disease in sheep and goats [2] and has long been suspected to be involved in the etiology of Crohn's Disease (CD), an inflammatory bowel disease (IBD) of humans [3]. MAP and/or CD are also associated with many other autoimmune diseases including multiple sclerosis [4][5][6][7][8][9][10][11][12][13], type I diabetes mellitus [14][15][16][17][18][19], rheumatoid arthritis [20][21][22], Sjogren's syndrome [23], asymmetric lateral sclerosis [24], systemic sclerosis, celiac disease [25], depression [26], thyroiditis [27], and the neurodegenerative diseases including Alzheimer's disease [28] and Parkinson's disease [29]. A diarrheal/wasting illness associated with infection with MAP has also been reported in non-human primates [30].…”
Section: Introductionmentioning
confidence: 99%
“…The in silico molecular modeling study demonstrated that the MAP_2694 295–303 peptide displays a binding affinity to MS-associated HLA-DR molecules [10]. Furthermore, a recent article has revealed high serum levels of antibodies against the MAP_2694 295–303 peptide in Japanese patients with MS (12 RRMS, 2 secondary progressive, and 1 primary progressive) and those with a clinically isolated syndrome (CIS) [11].…”
Section: Introductionmentioning
confidence: 99%